2016
DOI: 10.1167/iovs.15-18909
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Retinal Nerve Fiber Layer Vascular Microcirculation in Glaucoma Using Optical Coherence Tomography–Based Microangiography

Abstract: PurposeTo investigate the vascular microcirculation changes in the retinal nerve fiber layer (RNFL) in normal, glaucoma suspect, and open-angle glaucoma (OAG) groups using optical coherence tomography–based microangiography (OMAG).MethodsOne eye from each subject was scanned with a Cirrus HD-OCT 5000–based OMAG prototype system montage scanning protocol centered at the optic nerve head (ONH). Blood flow signals were extracted using OMAG algorithm. Retinal nerve fiber layer vascular microcirculation was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
113
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 40 publications
10
113
4
Order By: Relevance
“…Akagi et al 5 suggested that the superficial vessel density is a better indicator of nerve damage than the vasculature of the entire disc in high myopia. Recently, Chen et al 18 reported that a superficial blood flux index is more susceptible to glaucomatous damage than vessel density. Even though vascular insufficiency might occur in the prelaminar area of glaucomatous eyes, a complex interaction among the ocular perfusion pressure, oxygen tension, vasoactive substances, extracellular matrix, and IOP might minimize ischemia and mask impaired blood flow in the prelaminar area of the glaucomatous optic disc.…”
Section: Discussionmentioning
confidence: 99%
“…Akagi et al 5 suggested that the superficial vessel density is a better indicator of nerve damage than the vasculature of the entire disc in high myopia. Recently, Chen et al 18 reported that a superficial blood flux index is more susceptible to glaucomatous damage than vessel density. Even though vascular insufficiency might occur in the prelaminar area of glaucomatous eyes, a complex interaction among the ocular perfusion pressure, oxygen tension, vasoactive substances, extracellular matrix, and IOP might minimize ischemia and mask impaired blood flow in the prelaminar area of the glaucomatous optic disc.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased microvascular density was more severe in the inferior region in eyes with more superior visual field (VF) defect and vice versa. Similarly, Yarmohammadi et al 22 and Chen et al 23 reported that the vessel density within the RNFL was lower in eyes with primary open-angle glaucoma (POAG) than in glaucoma suspects and healthy eyes. Akagi et al 24 showed that the parapapillary retinal vessel density was reduced in the corresponding hemi-field in POAG eyes with hemi-field VF defect.…”
mentioning
confidence: 94%
“…There are a number of approaches one could use to contrast vasculature, each with its own advantages, but of interest here is a complex-signal based method because it provides more sensitive measurement to slow blood flow, such as in the functional capillary vessels (41,42). One such method whose high sensitivity has already been shown to be successful in the visualization of functional vasculatures in small animal models and human tissues, such as skin and eye (43)(44)(45) is optical microangiography (OMAG) (39,(46)(47)(48). The recent development of OMAG for imaging dynamic blood perfusion within tissue beds was heralded as one of the most significant extensions of conventional OCT, and has been successfully translated to clinical ophthalmic imaging (45,(49)(50)(51).…”
Section: Introductionmentioning
confidence: 99%
“…One such method whose high sensitivity has already been shown to be successful in the visualization of functional vasculatures in small animal models and human tissues, such as skin and eye (43)(44)(45) is optical microangiography (OMAG) (39,(46)(47)(48). The recent development of OMAG for imaging dynamic blood perfusion within tissue beds was heralded as one of the most significant extensions of conventional OCT, and has been successfully translated to clinical ophthalmic imaging (45,(49)(50)(51). Here, we present a clinical prototype OMAG system that was specially designed for dermatological applications for high resolution monitoring of the microcirculatory and structural features underlying the processes of wound healing in otherwise healthy skin.…”
Section: Introductionmentioning
confidence: 99%